Modem Information Communication Technologies and Tools for Supply Chain Management - Evelin Vatovec Krmac (Promet - Traffic&Transportation, 1970)
The paper presents the most important supply chain technologies,including the latest applications and software toolsused by companies that operate in the transportation and logisticsfields. The primary goals of these technologies are informationexchanges within and between organizations and/or managingsupply chain related data and activities. New electroniclogistics applications are increasingly being moved off proprietarysystems and private networks onto the intemet. With thee-commerce market exploding, portals are becoming a key elementin bringing together an enterprise's employees, businesspartners, and customers - the principle actors of every supplychain - through one interface, accessible via the intemet. Becauseof this capacity they are sometimes called e-supply chainmega portals.